Arsenic and Environmental Health: State of the Science and Future Research Opportunities - Carlin, Danielle J.; Naujokas, Marisa F.; Bradham, Karen D.; Cowden, John; Heacock, Michelle; Henry, Heather F.; Lee, Janice S.; Thomas, David J.; Thompson, Claudia; Tokar, Erik J.; Waalkes, Michael P.; Birnbaum, Linda S.; et al. (Environmental health perspectives, 2016)
Exposure to inorganic and organic arsenic compounds is a major public health problem that affects hundreds of millions of people worldwide. Exposure to arsenic is associated with cancer and noncancer effects in nearly every organ in the body, and evidence is mounting for health effects at lower levels of arsenic exposure than previously thought. Building from a tremendous knowledge base with > 1,000 scientific papers published annually with "arsenic" in the title, the question becomes, what questions would best drive future research directions? The objective is to discuss emerging issues in arsenic research and identify data gaps across disciplines. The National Institutes of Health's National Institute of Environmental Health Sciences Superfund Research Program convened a workshop to identify emerging issues and research needs to address the multi-faceted challenges related to arsenic and environmental health. This review summarizes information captured during the workshop. More information about aggregate exposure to arsenic is needed, including the amount and forms of arsenic found in foods. New strategies for mitigating arsenic exposures and related health effects range from engineered filtering systems to phytogenetics and nutritional interventions. Furthermore, integration of omics data with mechanistic and epidemiological data is a key step toward the goal of linking biomarkers of exposure and susceptibility to disease mechanisms and outcomes. Promising research strategies and technologies for arsenic exposure and adverse health effect mitigation are being pursued, and future research is moving toward deeper collaborations and integration of information across disciplines to address data gaps. Carlin DJ, Naujokas MF, Bradham KD, Cowden J, Heacock M, Henry HF, Lee JS, Thomas DJ, Thompson C, Tokar EJ, Waalkes MP, Birnbaum LS, Suk WA. 2016. Arsenic and environmental health: state of the science and future research opportunities. Environ Health Perspect 124:890-899; http://dx.doi.org/10.1289/ehp.1510209.